The religious dimensions of shared spaces: when and how religion matters in space-sharing arrangements - Numrich, Paul David (Lexington Books, 2023)
"Space sharing by groups is widespread in the United States, from commercial partnerships, to government and private sector joint use agreements, to the use of public facilities and commons. All space-sharing arrangements are similar in most respects, so what difference does it make when religious groups are involved?"--